Remodelling of the gut microbiota by hyperactive NLRP3 induces regulatory T cells to maintain homeostasis. Issue 1 (December 2017) - Yao, Xiaomin; Zhang, Chenhong; Xing, Yue; Xue, Guang; Zhang, Qianpeng; Pan, Fengwei; Wu, Guojun; Hu, Yingxin; Guo, Qiuhong; Lu, Ailing; Zhang, Xiaoming; Zhou, Rongbin; et al.
Abstract Inflammasomes are involved in gut homeostasis and inflammatory pathologies, but the role of NLRP3 inflammasome in these processes is not well understood. Cryopyrin-associated periodic syndrome (CAPS) patients with NLRP3 mutations have autoinflammation in skin, joints, and eyes, but not in the intestine. Here we show that the intestines of CAPS model mice carrying anNlrp3 R258W mutation maintain homeostasis in the gut. Additionally, such mice are strongly resistant to experimental colitis and colorectal cancer; this is mainly through a remodelled gut microbiota with enhanced anti-inflammatory capacity due to increased induction of regulatory T cells (Tregs ). Mechanistically, NLRP3R258W functions exclusively in the lamina propria mononuclear phagocytes to directly enhance IL-1β but not IL-18 secretion. Increased IL-1β boosts local antimicrobial peptides to facilitate microbiota remodelling. Our data show that NLRP3R258W -induced remodelling of the gut microbiota, induces local Tregs to maintain homeostasis and compensate for otherwise-detrimental intestinal inflammation. Inflammasomes are involved in gut homeostasis and inflammatory pathologies. The authors show that a hyperactive NLRP3 inflammasome maintains gut homeostasis through remodelling of the gut microbiota and induction of regulatory T cells.